Peran Orang Tua Dalam Membangun dan Menguatkan Fondasi Iman Anak Usia Dini - Veronika Wulan Setiawati; Intansakti Pius X (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2024)
The family plays a central role in forming children's faith, with parents as the main educators in physical and spiritual aspects. Religious education in the family is directed at acquiring knowledge and attitudes that demonstrate responsibility within the family, church and society. However, previous research shows that children's faith education often receives little attention because parents are busy, especially at an early age. This research aims to illustrate the important role of parents in forming the basis of children's faith, especially at an early age, and supporting their participation in religious activities. The research method used is a qualitative approach with a descriptive approach, using literature reviews from books, journals and related articles.